Microsurgical Transcranial Approach of 112 Paraoptic Meningiomas: A Single-Center Case Series. (18th November 2021) - Lefevre, Etienne; Terrier, Louis-Marie; Bekaert, Olivier; Simonneau, Adrien; Rogers, Alister; Vignal-Clermont, Catherine; Boissonnet, Hervé; Robert, Gilles; Lot, Guillaume; Chauvet, Dorian
Graphical Abstract: